A Transfer Learning-Based Efficient Deep-Learning Methodology for Multi-Class Classification of Endoscopy Frames - M, Madhura Prakash M; GN, L. Krishnamurthy (International Journal of Computer Sciences and Engineering, 2022)
Computer-aided detection and analysis of anatomical structures and pathology with the support of Artificial Intelligence aids the medical experts by contributing to better utilization of the expert’s focus time. The gastrointestinal (GI) tract can be assessed for the presence of several irregularities like ulcers, bleeding, inflammation, polyps, and tumor that can be present in several diseases ranging from precancerous lesions to cancer. These abnormalities differ in their appearance by having a different shape, size variation, color and texture differences, and they generally show up to be outwardly comparable to the regular regions in the GI tract. This presents a challenge in designing an efficient classifier that can handle intra-class variations. An endoscopy procedure is performed to detect and diagnose GI abnormalities and to observe the GI pathology. A sequence of video frames of the GI region is captured during the investigation of the tract. A flexible tube with a camera-fitted at the end is injected into the patient’s body through the oral or rectum during the procedure. The frames captured can be analyzed for abnormality classification and lesion segmentation. The analysis is challenging because the frames may have low contrast, uniform background, color variations and indefinite lesion shapes. This makes the segmentation and classification on these frames a challenging task. In this effort, a transfer learning-based deep learning architecture has been employed for performing the multi-class classification of endoscopy frames. The proposed model has been trained and tested on the widely available KVASIR dataset and an average accuracy of 81% has been achieved.